2012
DOI: 10.1111/j.1471-0528.2012.03297.x
|View full text |Cite
|
Sign up to set email alerts
|

Triaging women with ovarian masses for surgery: observational diagnostic study to compare RCOG guidelines with an International Ovarian Tumour Analysis (IOTA) group protocol

Abstract: Objective To compare guidelines from the Royal College of Obstetricians and Gynaecologists (RCOG) based on the Risk of Malignancy Index (RMI) with a protocol based on logistic regression model LR2 developed by the International Ovarian Tumour Analysis (IOTA) group for triaging women with an ovarian mass as low, moderate, or high risk of malignancy. Sample In all, 1938 women undergoing surgery for an ovarian mass.Methods RCOG guidelines use the RMI to triage women as low (RMI < 25), moderate (25-250), or high (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 27 publications
1
44
1
3
Order By: Relevance
“…However, referring patients to expert examiners with masses in which the SRs do not apply or with equivocal results of LR2 is advantageous as it leads to a reduction in the false-positive rate, while only minimally decreasing the sensitivity. In this study as well as in IOTA phase 2 data, SRs were inconclusive in 23% of patients, whereas LR2 results were equivocal in 17–18% of the same patients (Timmerman et al , 2010a; Van Calster et al , 2012). In other validation studies of the SRs, fewer patients had inconclusive results with reported percentages between 11 and 21% in different populations (Fathallah et al , 2011; Hartman et al , 2012; Alcázar et al , 2013; Sayasneh et al , 2013b).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, referring patients to expert examiners with masses in which the SRs do not apply or with equivocal results of LR2 is advantageous as it leads to a reduction in the false-positive rate, while only minimally decreasing the sensitivity. In this study as well as in IOTA phase 2 data, SRs were inconclusive in 23% of patients, whereas LR2 results were equivocal in 17–18% of the same patients (Timmerman et al , 2010a; Van Calster et al , 2012). In other validation studies of the SRs, fewer patients had inconclusive results with reported percentages between 11 and 21% in different populations (Fathallah et al , 2011; Hartman et al , 2012; Alcázar et al , 2013; Sayasneh et al , 2013b).…”
Section: Discussionsupporting
confidence: 53%
“…Several factors probably contribute to this failure to refer for specialist care, but the lack of effective preoperative strategies to evaluate ovarian tumours is certainly one of the most important factors (Miller and Ueland, 2012). Reports from the international ovarian tumour analysis (IOTA) multicentre studies phase 1, 1b, 2 and 4 (Timmerman et al , 2005, 2007, 2008, 2010a, 2010b; Van Holsbeke et al , 2009, 2012; Ameye et al , 2012; Kaijser et al , 2013; Sayasneh et al , 2013a, 2013b) have demonstrated that IOTA ultrasound-based approaches to characterise adnexal masses in the hands of physicians and sonographers with varying levels of experience outperform other established strategies such as use of individual biomarkers (serum CA-125), the Risk of Malignancy Index (RMI; Jacobs et al , 1990) or Risk of Ovarian Malignancy Algorithm (Moore et al , 2009), for the classification of ovarian pathology. Nevertheless, there is a paucity of comprehensive prospective studies comparing different diagnostic strategies for ovarian cancer diagnosis on the same study population.…”
mentioning
confidence: 99%
“…If at high risk, referral of the woman to a cancer center for a full staging procedure by a subspecialist gynecological oncologist is advised. A recent study by Van Calster et al has found that the IOTA protocol was more accurate for triage than the RCOG protocol [14].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal operative cytoreduction by a skilled surgeon combined with correct staging according to FIGO greatly improves distant results of management in ovarian cancer [3]. Modern imaging techniques and fast progress in laboratory tests have enabled a great step forward in diagnostic algorithms [4][5][6][7][8][9][10][11]. ROMA (Risk of Malignancy Algorithm) based on CA125 and the novel HE4 marker has recently emerged as a promising approach to the preoperative categorization of malignancy risk [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%